Clinical and histology features as predictor of severity of mucormycosis in post-COVID-19 patients: An experience from a rural tertiary setting in Central India. (February 2022) - Jain, Kavita; Surana, Akshay; Choudhary, Tej Singh; Vaidya, Sudhakar; Nandedkar, Shirish; Purohit, Manju
Background: An upsurge in cases of rhinosinusitis with or without associated orbital and/or cerebral involvement by mucormycosis has been observed in post-COVID-19 patients. Our objective is to evaluate the clinical and histopathology features of these patients to determine the severity and develop a scoring on the extent on tissue invasion. Method: We prospectively enrolled and analyzed 95 post-COVID-19 patients who presented with the invasive mucormycosis of the head and neck region. Clinical and histology details were noted in predesigned forms. Various histology variables were graded from I to III to propose a scoring system for the severity of the disease. Results: Mucormycosis was common in males with a mean age of 46.8 ± 11 years. Facial pain was the most common presenting complaint and 77% of the patients were diabetic. Most cases (n = 59) showed a moderate degree of neutrophilic infiltrate with ⩾50% tissue necrosis and angioinvasion in three or more vessels with a fungal load of 2+/3+. Histology severity grade III was observed in patients who died from cerebral mucormycosis (n = 3) and septicemia (n = 2) and in patients who had undergone orbital exenteration (n = 6). Conclusion: The histopathology and severity score classification was directly correlated with the outcome of the patients. Further evaluation and a larger study will help to validate the proposed scoring for its clinical use in all forms and causes of mucormycosis.